Analysis of four shield-driven tunnels with complex spatial relations in a clay stratum. (June 2022) - Hou, Yanjuan; Zhou, Mozhen; Zhang, Dingli; Fang, Qian; Sun, Zhenyu; Tian, Yuanhao
Highlights: Laboratory tests provide data for simulation using modified Cam-clay model. The influence zone partition of multi-line tunnels is obtained. The parameters in Peck formula for a clay stratum are determined and validated. An improved Peck formula is proposed for multiple-tunnel induced settlements. Abstract: The tunnelling-induced ground settlement is a key concern during urban underground construction. This paper examined the ground settlement caused by multi-line tunnelling with earth pressure balance shield in the clay stratum in Tianjin, China. Laboratory tests are conducted to determine the soil parameters used in the modified Cam-Clay model. The real-data numerical simulation achieves a good agreement with in-situ monitoring data. The influence zone partition of multi-line tunnel construction is obtained and then used to evaluate the safety risks. An improved Peck formula is proposed based on the combination of superposition, overlapping and grouting effects. The parameter ranges are calibrated by means of statistical and numerical analysis. This study provides a reliable reference and practical tool for design and construction of multiple tunnels in a clay stratum.